Representasi Patriarki dalam Film “Basri and Salma in A Never Ending Comedy” Menurut Feminis Eksistensialisme Beauvoir - Fernanda, Jenny; Sari, Rosnida; Arifiyanti, Jati (P3M Politeknik Negeri Media Kreatif, 2025)
The issue of patriarchy against women is widely voiced through various media, including film. Film serves as a platform that can advocate for societal problems. Myths, social norms, and the perpetuation of patriarchy can be vocally expressed in films, an example of which is Basri and Salma in a Never Ending Comedy. The existence of films can be a way of socialization that presents and voices issues of inequality to the public. This research aims to analyze the representation of patriarchy in the film Basri and Salma in a Never Ending Comedy based on the concept of Simone de Beauvoir's existentialist feminist theory using a qualitative research method with a Roland Barthes' semiotic approach. Based on the research, representations of inequality and discrimination against women were found, particularly on the topic of the normalization reality of a wife's obligation to provide an heir to her husband through her maternal function—which, of course, points to patriarchal practices.